2021
DOI: 10.3390/s21144876
|View full text |Cite
|
Sign up to set email alerts
|

Framework for In-Field Analyses of Performance and Sub-Technique Selection in Standing Para Cross-Country Skiers

Abstract: Our aims were to evaluate the feasibility of a framework based on micro-sensor technology for in-field analyses of performance and sub-technique selection in Para cross-country (XC) skiing by using it to compare these parameters between elite standing Para (two men; one woman) and able-bodied (AB) (three men; four women) XC skiers during a classical skiing race. The data from a global navigation satellite system and inertial measurement unit were integrated to compare time loss and selected sub-techniques as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In Para XC skiers, it has been shown that the varying terrain leads to substantial variation in speed, which is regulated by the selection of pacing strategies, subtechniques, and related kinematic patterns. 5 6 While this has not yet been investigated for Para XC skiers and biathletes, the aerobic energy contribution during races is expected to be similar as in their able-bodied counterparts, and in the range of 80%–95%. 7–10 Therefore, performance is mainly determined by a high peak oxygen uptake (V̇O 2peak ), the performance maximum rate of oxygen (V̇O 2max) and exercise efficiency.…”
Section: Sport-specific Demandsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Para XC skiers, it has been shown that the varying terrain leads to substantial variation in speed, which is regulated by the selection of pacing strategies, subtechniques, and related kinematic patterns. 5 6 While this has not yet been investigated for Para XC skiers and biathletes, the aerobic energy contribution during races is expected to be similar as in their able-bodied counterparts, and in the range of 80%–95%. 7–10 Therefore, performance is mainly determined by a high peak oxygen uptake (V̇O 2peak ), the performance maximum rate of oxygen (V̇O 2max) and exercise efficiency.…”
Section: Sport-specific Demandsmentioning
confidence: 99%
“…Para XC skiing and biathlon are endurance sports, in which athletes compete in race courses consisting of undulating terrain with uphill, flat and downhill segments. In Para XC skiers, it has been shown that the varying terrain leads to substantial variation in speed, which is regulated by the selection of pacing strategies, subtechniques, and related kinematic patterns 5 6. While this has not yet been investigated for Para XC skiers and biathletes, the aerobic energy contribution during races is expected to be similar as in their able-bodied counterparts, and in the range of 80%–95% 7–10.…”
Section: Sport-specific Demandsmentioning
confidence: 99%
“…The topic of article [ 9 ] was related to para-athletic cross-country (XC) skiing. The paper's aims were to evaluate the feasibility of a framework based on micro-sensor technology for, firstly, in-field analyses of performance and, secondly, sub-technique selection in the field by using it to compare different parameters between elite standing para-athletic and able-bodied XC skiers during a classical skiing race.…”
mentioning
confidence: 99%